Micro-distribution of arsenic and polycyclic aromatic hydrocarbons and their interaction in Pteris vittata L. (15th September 2021) - Liao, Xiao-Yong; Gong, Xue-Gang; Zhang, Li-Li; Cassidy, Daniel P.
Abstract: Interactive effects of inorganic arsenic (As) species and polycyclic aromatic hydrocarbons (PAHs) on their uptake, accumulation and translocation in the hyperaccumulator Pteris vittata L. ( P. vittata ) were studied hydroponically. The presence of PAHs hindered As uptake and acropetal translocation by P. vittata, decreasing As concentrations by 29.8%–54.5% in pinnae, regardless of the initial As speciation. The inhibitive effect of PAHs was 1.6–8.7 times greater for arsenite [As(III)] than for arsenate [As(V)]. Similarly, inorganic As inhibited the uptake of fluorene (FLU) and benzo[a]pyrene (BaP) by P. vittata roots by 0.4%–21.7% and by 33.1%–69.7%, respectively. Interestingly, coexposure to As and PAHs slightly enhanced the translocation of PAHs by P. vittata with their concentrations increased 0.3 to 0.8 times in shoots, except for the As(III)+BaP treatment. The antagonistic interaction between As and PAHs uptake is likely caused by competitive inhibition or oxidative stress injury. By using synchrotron radiation micro X-ray fluorescence imaging, high concentrations of As were found distributed throughout the microstructures far from main vein of the pinnae when coexposed with PAHs, the opposite of what was observed with exposure to As only. PAHs could also significantly inhibit the accumulation and distribution of As in vascular bundles in rachis treated with As(III). The results of two-photon laser scanning confocal microscopy revealed that PAHs were mainly distributed in the vascular cylinder, epidermal cells, vascular bundles, epidermis and vein tissues, and this was independent of As speciation and treatment. This work offers new positive evidence for the interaction between As and PAHs in P. vittata, presents new information on the underlying mechanisms for interactions of As and PAHs affecting their uptake and translocation within P. vittata L., and provides direction for future research on the mechanisms of PAHs uptake by plants. Graphical abstract: Image 1 Highlights: Both FLU and BaP hindered As uptake and acropetal translocation by P. vittata regardless of the initial As speciation. The presence of Arsenate would promote the transfer of FLU and BaP from roots to shoots. This study revealed the subcellular movement and distribution of PAHs in P. vittata. Abstract : Antagonistic interaction was found between PAHs and As uptake in P. vittata, while the distribution of PAHs in plant was independent of As.